Working with corpora in the translation classroom - Krüger, Ralph (Zakład Filologii Angielskiej Wydział Pedagogiczno-Artystyczny Uniwersytetu im. Adama Mickiewicza w Kaliszu, 2012)
This article sets out to illustrate possible applications of electronic corpora in the translation classroom. Starting with a survey of corpus use within corpus-based translation studies, the didactic value of corpora in the translation classroom and their epistemic value in translation teaching and practice will be elaborated. A typology of translation practice-oriented corpora will be presented, and the use of corpora in translation will be positioned within two general models of translation competence. Special consideration will then be given to the design and application of so-called Do-it-yourself (DIY) corpora, which are compiled ad hoc with the aim of completing a specific translation task. In this context, possible sources for retrieving corpus texts will be presented and evaluated and it will be argued that, owing to time and availability constraints in real-life translation, the Internet should be used as a major source of corpus data. After a brief discussion of possible Internet research techniques for targeted and quality-focused corpus compilation, the possible use of the Internet itself as a macro-corpus will be elaborated. The article concludes with a brief presentation of corpus use in translation teaching in the MA in Specialised Translation Programme offered at Cologne University of Applied Sciences, Germany.
Keywords: corpora; translation classroom; do-it-yourself (DIY) corpora; Web as macro-corpus